Critical Thinking for Intelligence Analysis for Nigerian Students: Evaluating the Pedagogical Challenges in Real Life Scenarios - Isa, Awal; Nte, Ngboawaji Daniel; Baba-Ahmadu, Abdulaziz (Indonesian Educational Administration and Leadership Journal (IDEAL), 2023)
Abstract Twenty-first Century intelligence issues involve uncertainty, mysteries, and risk. This differs from the 20th Century paradigms of security, secrets, and prevention. Analysis of current complex issues requires its practitioners’ novel approaches including a productively imaginative process of inquiry. Questions analysts ask not only serve as devices for attracting existing evidence, but also as devices for generating new evidence not presently considered. In this way, analysts meticulously examine complex issues and aided by technology, are predisposed to creating novel actionable intelligence and preventing strategic surprises. Normatively, this brand of reasoning is at odds with how most people, including intelligence analysts naturally think, as people seek to confirm the first answer to a problem they discover, selectively use evidence to support that position even when there are compelling pieces of evidence that an alternative hypothesis may actually be the correct one. That people routinely fall prey to such poor thinking is well documented and indeed, most commercial advertisers strive to take advantage of this, so do adversaries. One element of most intelligence failures includes poor thinking on the part of analysts. Poor thinking which adversaries usually take advantage of. So how can analysts avoid such thinking? One solution is to teach intelligence analysts to think critically. Critical thinking therefore provides structure to the reasoning processes that identify for analysts where they are most likely to go astray. It offers a means for self-reflective reasoning that leads to improved thinking. If such thinking is aided by structured analytic techniques, then analysts will, and do improve on how they resolve security-laden issues with clarity and effective response.